Is fairness blind? The effect of framing on preferences for effort-sharing rules - Fredrik Carlsson; Mitesh Kataria; Elina Lampi; Åsa Löfgren; Thomas Sterner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
By using a choice experiment, this paper focuses on citizens' preferences for effort-sharing rules of how carbon abatement should be shared among countries. We find that Swedes do not rank the rule favoring their own country highest. Instead, they prefer the rule where all countries are allowed to emit an equal amount per person, a rule that favors Africa at the expense of high emitters such as the U.S. The least preferred rule is reduction proportional to historical emissions. Using two different treatments, one where the respondents were informed about the country names and one where the country names were replaced with anonymous labels A-D, we also test whether people's preferences for effort-sharing rules depend on the framing of the problem. We find that while the ranking of the principles is the same in both treatments, the strength of the preferences is significantly increased when the actual names of the countries are used.
Keywords: D03; Q54; 330; climate change; fairness; framing; ethics; effort-sharing rules; Klimaveränderung; Klimaschutz; Framing; Gerechtigkeit; Ethik; Verhaltensökonomik; Schweden